MEDIA HAPPY NOTE BERUANG CANVA UNTUK PEMBELAJARAN TEMATIK SENI RUPA DAN BAHASA INDONESIA - Prihati, Wahyuning; Insanul Qisti Barriyah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
The use of innovative and interactive learning media is crucial to support the implementation of thematic learning in schools. This study aims to develop a Happy Note Beruang media based on the Canva application to facilitate thematic learning in Visual Arts and Indonesian Language. The Canva application provides various features and tools that make it easy for teachers to design and develop engaging and interactive learning content. Through Canva, teachers can create visual designs, infographics, presentations, and other learning materials that are tailored to the needs and characteristics of students. In addition, Canva also supports collaboration between teachers or between teachers and students in developing learning media together. This can encourage students' creativity and critical thinking skills. An observation sheet is used to determine the effectiveness of using the Canva-based Happy Note Beruang media in thematic learning of Visual Arts and Indonesian Language. The observation sheet can cover aspects such as: 1) students' interest and enthusiasm in using the learning media, 2) students' interaction and active involvement during the learning process, 3) students' understanding of the material presented through the media, 4) the ease of use of the media for teachers and students, and 5) the suitability of the media with the objectives of thematic learning. By using the observation sheet, teachers can collect empirical data on the impact of using the Happy Note Beruang media in improving the quality of thematic learning in Visual Arts and Indonesian Language.